Temperate Kelp Forest Collapse by Fish Herbivory: A Detailed Demographic Study - Barrientos, Sara; Piñeiro-Corbeira, Cristina; Barreiro, Rodolfo (Frontiers in Marine Science, 2022)
Kelps dominate rocky shores in temperate latitudes, acting as important foundation species. Recently, kelp forests have received growing attention for their decline around the world. Climate change is one of the main drivers of their deforestation, both through abiotic stress and/or distortion of biotic interactions. In NW Spain, golden kelp (Laminaria ochroleuca) forests have recently declined in some areas due to excessive grazing. To further investigate the mechanisms behind this decline, a thorough one-year seasonal demographic study was carried out on eight golden kelp reefs: four healthy and four degraded by herbivory. Kelps covered the full range of size classes throughout the year on healthy reefs. By contrast, only small, newly recruited kelps were found on degraded reefs in spring-summer, because excessive herbivory in autumn-winter caused a total collapse of kelp populations on a reef-scale (i.e. all kelps reduced to inviable stubs with no blade and no growth meristem). Bite marks in kelps covering all size classes showed that fishes, instead of invertebrates, were the culprits of the excessive herbivory. Recent studies, mostly conducted in the Indo-Pacific, also found that fish herbivory, alone or in combination with abiotic stressors, can maintain a canopy-free state in kelp reefs. To the best of our knowledge, this is the first time that fish is also shown to cause the collapse of entire kelp forests on a reef scale in the temperate Atlantic. The implications of this finding for the management and potential recovery of degraded reefs are discussed.